2018
DOI: 10.1590/s0100-204x2018000300002
|View full text |Cite
|
Sign up to set email alerts
|

Early selection and classification of yerba mate progênies

Abstract: The objective of this work was to evaluate the feasibility of early selection of open-pollinated yerba mate (Ilex paraguariensis) progenies, and to classify the best parents and candidates for clones. The germplasm is composed of 140 progenies collected from areas within the natural distribution of the species in Southern Brazil and a commercial genotype (control). The experiment was established in Ivaí, in the state of Paraná, Brazil, in March 1997, in randomized complete blocks, with ten replicates, and line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
9
3
1
Order By: Relevance
“…For example, Sturion et al (2017) estimated an individual heritability of 0.17 for LMW at 18.5 years of age, a value and age similar to those of the present study. However, in contrast to our findings, Wendling et al (2018) reported higher heritability estimates for the LMW trait at various ages, including 0.59 at age 2.5, 0.79 at age 4.5, 0.88 at age 6.5, and 0.65 at age 18.7. Concerning the crown traits, low to high values of h 2 were obtained (0.08 and 0.74), with average values of 0.38 for CH, 0.21 for CD, and 0.37 for CV (Table 2).…”
Section: Genetic Variance Heritability and Additive Genetic Coefficie...contrasting
confidence: 99%
“…For example, Sturion et al (2017) estimated an individual heritability of 0.17 for LMW at 18.5 years of age, a value and age similar to those of the present study. However, in contrast to our findings, Wendling et al (2018) reported higher heritability estimates for the LMW trait at various ages, including 0.59 at age 2.5, 0.79 at age 4.5, 0.88 at age 6.5, and 0.65 at age 18.7. Concerning the crown traits, low to high values of h 2 were obtained (0.08 and 0.74), with average values of 0.38 for CH, 0.21 for CD, and 0.37 for CV (Table 2).…”
Section: Genetic Variance Heritability and Additive Genetic Coefficie...contrasting
confidence: 99%
“…Yerba mate (Ilex paraguariensis St. Hil) is a native woody tree from Araucaria Forest (Mixed Ombrophilous Forest) in South America [1,2], cultivated in Argentina, Paraguay, Uruguay, and southern Brazil, where its leaves are ground and have been used to produce a tea beverage widely consumed locally [3].…”
Section: Introductionmentioning
confidence: 99%
“…Based field evaluations and the results of genetic-statistical analyzes for the traits at two (height and crown diameter) and three years old (visually estimated biomass, weighed biomass and thick branch mass), it is recommended to continue evaluating these experiments in the coming years. These considerations are also based on the evaluation of feasibility of early selection for yerba mate performed by Wendling et al (2018). In this case, early selection is effective at 6.5 years for the trait commercial biomass of leaves and branches smaller than 7 mm.…”
Section: Resultsmentioning
confidence: 99%